Predictive Value of Class III D Cytological Diagnosis (Munich II, Low and Moderate Dysplasia) and Additional High-risk HPV Testing - Ziemke, P. (Geburtshilfe und Frauenheilkunde, 2012)
The validity of cytological diagnostic procedures for the detection of pre- and early cervical cancer stages is limited due to biological conditions, the uncertainty of cell sampling, and the subjective nature of microscopic assessment. Particularly in class III D cases (Munich II) this can lead to a stigmatization of patients and uncertainty with regard to further clinical follow-up and therapy. Prior to carrying out additional investigations such as high-risk HPV testing or the examination of biomarkers, the positive predictive values of patients with a class III D cytological diagnosis need to be assessed in routine practice. To this end, all relevant data from patients from our practice classed as class III D (pap smears) between 2002 and 2008 (n = 1190; 38.2 % histological diagnosis = therapeutic endpoint) and their current HPV status were recorded. Cytology, histology, persistence, age and follow-up were recorded. The database was used for comparative statistical analysis. Overall, the positive predictive value of conventional pap smear for CIN 2+ was calculated to be 32.3 % (mean follow-up: 39.7 months). The following values were calculated for high-risk HPV testing: sensitivity 94.8 %, specificity 39 %, positive predictive value 42.8 %, negative predictive value 94 %. The additional information obtained from high-risk HPV testing resulted in a significantly better positive predictive value only in patients older than 40 years. However, there was no evidence for an individual risk stratification approach which would reduce uncertainty in the management of III D patients.
Keywords: cervical carcinoma; cervical cytology; class III D; dysplasia; CIN